STUDIES ON THE BIOLUBRICANT PROPERTIES OF MORINGA OLEIFERA SEED OIL: CORRELATING VISCOSITY AND FATTY ACID COMPOSITION - Louis M., NWOKOCHA; Toyib B., AREMU (Malaysian Journal of Science, 2017)
This study examined the characteristics of Moringa oleifera seed oil as a biolubricant. The study covered the physicochemical and rheological characteristics of the seed oil. The seed yielded 37.9% oil with the following physicochemical properties: peroxide value (1.655 meq kg-1), saponification value (154.5 mg KOH g-1), and acid value (9.724 mg KOH g-1).The rheological characteristics of M. oleifera oil showed the oil was solid at 10.1oC and exhibited flow properties typical of vegetable oils in the temperature range 30 to 70oC however it exhibited thermal instability at 90oC as indicated by the entirely shear thinning properties of the oil attributed to polymerization of the oil to gum. The oil had oleic acid (72.73%) as the principal fatty acid. The high viscosity of M. oleifera oil (0.06078 Pas, 30oC) correlates with its high percentage of long chain fatty acids (C â‰¥16 = 99.86%), and the high oleic acid composition indicates a potential for application as a biolubricant. Keywords: Moringa oleifera oil, biolubricant, physicochemical, rheological, fatty acid composition